Pengaruh Beban Kerja, Komunikasi, dan Konflik Kerja terhadap Kepuasan Kerja Karyawan PT Multi Garmenjaya - Siti Haniah; Siska Fajar Kusuma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the influence of workload, communication, and work conflict both partially and simultaneously on employee job satisfaction at PT Multi Garmenjaya. The research method used is the survey method. In collecting this data using direct observation and distribution of questionnaires in the field related to the object of research. The population in this study were employees of PT Multi Garmenjaya. The sample in this study was part of PT Multi Garmenjaya employees, totalling 112 employees. This sampling used a saturated sampling method. The results of the study using path analysis found that workload, communication, and work conflict both partially and simultaneously had a significant effect on the job satisfaction of PT Multi Garmenjaya employees.